The Relationship between The Adoption of Innovation and The Communication Channel of Madura Cattle Farmers - Ary Bakhtiar; Ridha Rizki Novanda (JOURNAL OF SOCIOECONOMICS AND DEVELOPMENT, 2018)
Madura cattle are one type of local cattle developed and maintained by some Madurese farmers. The adoption of technology is a concept used to absorb new innovative technologies in relation to the development of Madura cattle breeding businesses. Communication channels hold an important role in delivering information to farmers. Active communication channels can facilitate farmers in absorbing information, so the purpose of this study is to analyze how the relationship between communication channels with the adoption of innovation in Madura cattle farmers in the Madura islands. This research was carried out in August 2018 by using secondary data with the research findings taken were Sumenep Regency, Pamekasan, and Bangkalan. The samples taken are 60 people and processed by using Spearman rank correlation analysis method. The results showed that the communication channel is significantly related to knowledge with a correlation coefficient of 0.314. Beside that, the communication channel is significantly related to the decision with the Spearman correlation value of 0.046. Meanwhile, the stages of implementation, implementation, and confirmation do not have a relationship with the communication channel. The adoption of innovative technology relies heavily on the communication channels chosen to transmit technological innovation. The selection of the right extension agents is directly to demonstrate technological innovation to farmers. Thus, the stakeholders are expected to be able to provide direct counseling to increase knowledge and decisions to adopt innovative technology.JEL Classification: O31, Q12, Q16